Motor Third Party Liability Insurance in Russia: Gaining Competitive Advantage - Rogozin, Konstantin (2006)
The report identifies which factors of service-based offerings are of utmost importance for customers, considers the areas of MTPL insurance that may contain a potential sources for differentiation, and stresses importance of knowing customer needs and requirements. This report should assist the insurance company to categorise and systematise relevant information so as to develop a product position, which may give a competitive advantage.